Canopy-Mediated Hydrodynamics Contributes to Greater Allelic Richness in Seeds Produced Higher in Meadows of the Coastal Eelgrass Zostera marina - Follett, Elizabeth; Hays, Cynthia G.; Nepf, Heidi (Frontiers in Marine Science, 2019)
Seagrass meadows, which mediate ocean acidity and turbidity, sequester carbon, and increase biodiversity by providing shelter for larvae and small fish, are among the fastest disappearing ecosystems worldwide. Seagrasses are ecosystem engineers, creating distinct regions of enhanced and diminished flow and turbulent mixing, dependent upon canopy physical parameters, such as canopy density and blade morphology, which in turn impact the transport of pollen, sediment, and nutrients. The health and resilience of seagrass meadows increases with intraspecies genetic diversity, which depends on successful sexual reproduction and the transport of pollen particles between reproductive shoots, which in turn depends on the hydrodynamic conditions created by the meadow. This paper explored the transport of pollen grains in seagrass meadows using a random walk model. The model was parameterized with profiles of mean velocity and eddy diffusivity derived as functions of shoot density, canopy height, canopy shear velocity, canopy drag coefficient, and blade width, and validated with experimental measurements of a tracer plume evolving in a submerged model canopy. Model results showed that release at the top of the canopy led to significantly greater dispersal than release within the canopy, which was consistent with observed patterns of genetic diversity in Zostera marina seeds collected from coastal Massachusetts meadows. Specifically, seeds produced from upper inflorescences had greater allelic richness than seeds from lower inflorescences on the same reproductive shoot, and were the product of a greater number of fathers, reflecting the greater in-canopy pollen movement farther from the bed. Pollen grains modeled with a realistic elongated shape experienced significantly higher rates of capture by the canopy relative to spherical grains of the same volume. The effect of submergence depth (the ratio of water depth to canopy height) on pollen dispersal depended on the nature of the surface boundary: when pollen reflected off the water surface, the mean travel distance before pollen capture decreased with decreasing submergence depth. In contrast, when pollen accumulated at the water surface, surface transport increased pollen dispersal distances, especially at low submergence depths.